Sulfur Dioxide Activates Cl-/HCO3- Exchanger via Sulphenylating AE2 to Reduce Intracellular pH in Vascular Smooth Muscle Cells - Wang, Yi; Wang, Xiuli; Chen, Selena; Tian, Xiaoyu; Zhang, Lulu; Huang, Yaqian; Tang, Chaoshu; Du, Junbao; Jin, Hongfang (Frontiers in Pharmacology, 2019)
Sulfur dioxide (SO2) is a colorless and irritating gas. Recent studies indicate that SO2 acts as the gas signal molecule and inhibits vascular smooth muscle cell (VSMC) proliferation. Cell proliferation depends on intracellular pH (pHi). Transmembrane cystein mutation of Na+- independent Cl-/HCO3- exchanger (anion exchanger, AE) affects pHi. However, whether SO2 inhibits VSMC proliferation by reducing pHi is still unknown. Here, we investigated whether SO2 reduced pHi to inhibit the proliferation of VSMCs and explore its molecular mechanisms. Within a range of 50–200 μM, SO2 was found to lower the pHi in VSMCs. Concurrently, NH4Cl pre-perfusion showed that SO2 significantly activated AE, whereas the AE inhibitor 4,4′-diisothiocyanatostilbene- 2,20-disulfonic acid (DIDS) significantly attenuated the effect of SO2 on pHi in VSMCs. While 200 μM SO2 sulphenylated AE2, while dithiothreitol (DTT) blocked the sulphenylation of AE2 and subsequent AE activation by SO2, thereby restoring the pHi in VSMCs. Furthermore, DIDS pretreatment eliminated SO2-induced inhibition of PDGF-BB-stimulated VSMC proliferation. We report for the first time that SO2 inhibits VSMC proliferation in part by direct activation of the AE via posttranslational sulphenylation and induction of intracellular acidification.